PERAN SISTEM INFORMASI MANAJEMEN (SIM) DALAM MENINGKATKAN KOLABORASI TIM DAN INOVASI DI LINGKUNGAN KERJA - Pratama Wirayudha Nasution; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Management Information Systems (MIS) play an important role in enhancing Team collaboration and promoting innovation in modern work environments. This Article aims to examine the role of SIM in strengthening interactions between team Members and accelerating the innovation process through the use of information Technology. The research method used involves a study of recent literature from the Last five years as well as case studies from organizations that have adopted SIM. The Results show that SIM can improve information flow, strengthen cross-departmental Team collaboration, and create space for the development of innovative new ideas. The research also identified challenges faced in implementing SIM in organizations.